Implementation and impact of an online tool used in primary care to improve access to financial benefits for patients: a study protocol. Issue 10 (22nd October 2017) - Aery, Anjana; Rucchetto, Anne; Singer, Alexander; Halas, Gayle; Bloch, Gary; Goel, Ritika; Raza, Danyaal; Upshur, Ross E G; Bellaire, Jackie; Katz, Alan; Pinto, Andrew David
Abstract : Objectives: Addressing the social determinants of health has been identified as crucial to reducing health inequities. However, few evidence-based interventions exist. This study emerges from an ongoing collaboration between physicians, researchers and a financial literacy organisation. Our study will answer the following: Is an online tool that improves access to financial benefits feasible and acceptable? Can such a tool be integrated into clinical workflow? What are patient perspectives on the tool and what is the short-term impact on access to benefits? Methods: An advisory group made up of patients living on low incomes and representatives from community agencies supports this study. We will recruit three primary care sites in Toronto, Ontario and three in Winnipeg, Manitoba that serve low-income communities. We will introduce clinicians to screening for poverty and how benefits can increase income. Health providers will be encouraged to use the tool with any patient seen. The health provider and patient will complete the online tool together, generating a tailored list of benefits and resources to assist with obtaining these benefits. A brief survey on this experience will be administered to patients after they complete the tool, as well as a request to contact them in 1 month. Those who agree to be contacted will be interviewed on whether the intervention improved access to financial benefits. We will also administer an online survey to providers and conduct focus groups at each site. Ethics and dissemination: Key ethical concerns include that patients may feel discomfort when being asked about their financial situation, may feel obliged to complete the tool and may have their expectations falsely raised about receiving benefits. Providers will be trained to address each of these concerns. We will share our findings with providers and policy-makers interested in addressing the social determinants of health within healthcare settings. Trial registration number: Clinicaltrials.gov: NCT02959866 . Registered 7 November 2016. Retrospectively registered. Pre-results.